Clinical and neural effects of six-week administration of oxytocin on core symptoms of autism. (3rd September 2015) - Watanabe, Takamitsu; Kuroda, Miho; Kuwabara, Hitoshi; Aoki, Yuta; Iwashiro, Norichika; Tatsunobu, Natsubori; Takao, Hidemasa; Nippashi, Yasumasa; Kawakubo, Yuki; Kunimatsu, Akira; Kasai, Kiyoto; Yamasue, Hidenori
Abstract : In a double-blind placebo-controlled trial, Watanabe et al. show that six-week oxytocin administration reduces core social symptoms of autism, increases resting-state functional connectivity in medial prefrontal cortex, and mitigates abnormalities in behavioural and neural responses during a social judgement task. The findings suggest clinical benefits of continual oxytocin use. Abstract : Abstract : Autism spectrum disorder is a prevalent neurodevelopmental disorder with no established pharmacological treatment for its core symptoms. Although previous literature has shown that single-dose administration of oxytocin temporally mitigates autistic social behaviours in experimental settings, it remains in dispute whether such potentially beneficial responses in laboratories can result in clinically positive effects in daily life situations, which are measurable only in long-term observations of individuals with the developmental disorder undergoing continual oxytocin administration. Here, to address this issue, we performed an exploratory, randomized, double-blind, placebo-controlled, crossover trial including 20 high-functional adult males with autism spectrum disorder. Data obtained from 18 participants who completed the trial showed that 6-week intranasal administration of oxytocin significantly reduced autism core symptoms specific to social reciprocity, which was clinically evaluated by Autism Diagnostic Observation Scale ( P = 0.034, P FDR < 0.05, Cohen's d = 0.78). Critically, the improvement of this clinical score was accompanied by oxytocin-induced enhancement of task-independent resting-state functional connectivity between anterior cingulate cortex and dorso-medial prefrontal cortex ( rho = –0.60, P = 0.011), which was measured by functional magnetic resonance imaging. Moreover, using the same social-judgement task as used in our previous single-dose oxytocin trial, we confirmed that the current continual administration also significantly mitigated behavioural and neural responses during the task, both of which were originally impaired in autistic individuals (judgement tendency: P = 0.019, d = 0.62; eye-gaze effect: P = 0.03, d = 0.56; anterior cingulate activity: P = 0.00069, d = 0.97; dorso-medial prefrontal activity: P = 0.0014, d = 0.92; all, P FDR < 0.05). Furthermore, despite its longer administration, these effect sizes of the 6-week intervention were not larger than those seen in our previous single-dose intervention. These findings not only provide the evidence for clinically beneficial effects of continual oxytocin administration on the core social symptoms of autism spectrum disorder with suggesting its underlying biological mechanisms, but also highlight the necessity to seek optimal regimens of continual oxytocin treatment in future studies.